2007
DOI: 10.1097/aud.0b013e3181576cba
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Evoked Response to Gaps in Noise: Within-Channel and Across-Channel Conditions

Abstract: Objectives-The objective of this study was to describe the cortical evoked response to silent gaps in a group of young adults with normal hearing using stimulus conditions identical to those used in psychophysical studies of gap detection. Specifically, we sought to examine the P1-N1-P2 auditory evoked response to the onsets of stimuli (markers) defining a silent gap for withinchannel (spectrally identical markers) and across-channel (spectrally different markers) conditions using four perceptually-equated gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
73
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(95 citation statements)
references
References 64 publications
(135 reference statements)
19
73
2
1
Order By: Relevance
“…The latter enhancement was further significantly stronger than the former (t 13 ϭ 2.9, p Ͻ 0.02). The timing of these enhancements was consistent with that reported by EEG studies on gap detection in noise (Michalewski et al, 2005;Pratt et al, 2005;Lister et al, 2007), tones (Heinrich et al, 2004), or noiseinterrupted tones (Riecke et al, 2009b). They further matched previously observed increases in 4 Hz power to sound onsets and offsets (Makeig, 1993;Riecke et al, 2009b).…”
Section: Neural On/off Responses To the Missing Vowel Portionsupporting
confidence: 90%
“…The latter enhancement was further significantly stronger than the former (t 13 ϭ 2.9, p Ͻ 0.02). The timing of these enhancements was consistent with that reported by EEG studies on gap detection in noise (Michalewski et al, 2005;Pratt et al, 2005;Lister et al, 2007), tones (Heinrich et al, 2004), or noiseinterrupted tones (Riecke et al, 2009b). They further matched previously observed increases in 4 Hz power to sound onsets and offsets (Makeig, 1993;Riecke et al, 2009b).…”
Section: Neural On/off Responses To the Missing Vowel Portionsupporting
confidence: 90%
“…In terms of the effect of gap duration on ACC latency, the findings have not been consistent. Whereas some researchers found a significant effect (Pratt et al, 2005; Lister et al, 2007), other researchers reported no effect at all (Michalewski et al, 2005). In addition, the effect of intensity change on ACC latency is still unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Jones and colleagues (Jones et al, 1998; Jones and Perez, 2001, 2002) reported that the ACC response could also be recorded in response to changes in pitch and/or timbre of synthesized music. In addition, several studies have shown that the ACC response can be recorded using ongoing stimuli that contain silent gaps of various durations (Michalewski et al, 2005; Pratt et al, 2005, 2007; Lister et al, 2007; Atcherson et al, 2009). Results of these studies showed that the ACC amplitude increased with increasing magnitude of acoustic changes in intensity (Martin and Boothroyd, 2000; Harris et al, 2007; Dimitrijevic et al, 2009, 2011), spectrum (Harris et al, 2008; Dimitrijevic et al, 2009, 2011), and gap duration (Michalewski et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a repeating sound at a random frequency and a repeating three-sound pattern appearing after random frequency sounds have been found to be evoking magnetic 100 (M100) responses [electroencephalography (EEG) N1 response] in the root mean square amplitude waveform of magnetoencephalography recordings [5,6] . In fact, cortical implications of auditory processes, ranging from the detection of sound onset to the detection of frequency changes as well as the detection of embedded gaps in continuous noise, are reflected on N1 responses, the magnetic counterpart of which is the M100 response [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%